How Does Changing "One-Size-Fits-All" to Differentiated Instruction Affect Teaching?. Issue 1 (March 2019) - Bondie, Rhonda S.; Dahnke, Christine; Zusho, Akane
This rigorous literature review analyzed how 28 U.S.-based research studies conducted between 2001 and 2015 have defined, described, and measured changes in teaching practices related to implementation of Differentiated Instruction (DI) in P–12 classrooms. Research questions examined frameworks that defined DI, classroom operationalization of DI, key barriers and facilitators, and how changes in teacher practices across studies did not lead to a common definition of DI. Extracted data were analyzed by study type, DI purpose, theoretical framework, research questions, methodology, analysis method, expected/reported change in teacher practice, expected/reported impact on student learning, key barriers, facilitators, contextual factors, and implications for teaching and research. Findings demonstrated how the many different frameworks used to define DI shaped a variety of changes to teacher practices and roles. The purpose of DI varied widely from a systematic response to policy to informal teacher perception of student differences. Barriers included the DI decision source (institution vs. teacher). Facilitators focused on teacher view of time, resources, control, and dispositions toward differences and ambiguity. The need for systematic replicable studies with greater methodological rigor is discussed and a more integrative definition of DI focused on teacher instructional reasoning and decision making is proposed for future research.